How do you simplify #x^-4 (x^2 + x - 3)#?

1 Answer
Jun 15, 2015

Answer:

#= color(blue)(x^-2 + x^-3 - 3.x^-4#

Explanation:

#x^-4 (x^2 + x - 3)#

Here , we need to multiply #color(red)(x^-4# with every term within the bracket.

#color(red)(x^-4) .x^2 +color(red)( x^-4).x^1 -color(red)( x^-4).3#

Note:
#color(blue)(a^m . a^n = a^(m+n)#
Applying the above mentioned property to the exponents of #x#

#= x^(-4+2) + x^(-4+1) - (x^-4).3#
#= x^-2 + x^-3 - (x^-4).3#
#= color(blue)(x^-2 + x^-3 - 3.(x^-4)#